Evaluation of variables responsible for hospital mortality in patients with rheumatic heart disease undergoing double valve replacement - Fernandes,André Maurício Souza (2014)
Objective: To describe the hospital mortality and associated clinical and echocardiographic variables in patients with rheumatic disease who underwent double valve replacement surgery. Methods: This is a cross sectional descriptive study of mortality, performed in a referral hospital in Salvador, Bahia. Records from patients with rheumatic disease who underwent double valve replacement surgery during the years 2007-2011 were analyzed. Results: The studied sample comprises 104 patients and 60 (57.7%) were male. The mean age was 38.04±14.45. Sixty five bioprostheses and 38 mechanical prostheses were used in these patients at the time of surgery. There were statistically significant differences between the two groups, when we analyzed the following variables: the mean age (36.30±13.03 vs. 45.35±17.8 years-old, P=0.011), mean hemoglobin (11.10±2.19 vs. 9.22±2.26 g/dL, P=0.002), mean hematocrit (34.22±5.86 vs. 28.44±6.62%, P<0.001). New York Heart Association functional class III and IV (NYHA) (P=0.022) was statistically associated with mortality. Conclusion: We concluded that the mean hemoglobin/hematocrit level and the NYHA functional class was the major variables associated to the mortality among these patients. Based on these data one may concern about the patient best moment for surgery and the patient hemoglobin level.